THE CRITERIA FOR MORPHOLOGICAL CLASSIFICATION OF PF GALAXY CLUSTERS - Panko, E. A. (Одеські астрономічні публікації, 2013)
The morphological types of galaxy clusters resulting from their out ward appearance is physically related to the clusters and their member galaxies. Presented here is an adopted system of morphological types of galaxy clusters based on the Zwicky, Boutz&Morgan, Rood&Sastry, and L´opez-Cruz systems. The adopted types are suitable for automated classification of galaxy clusters from The Catalogue of Galaxy Clusters and Groups (Panko& Flin 2006). Numerical criteria describing 6 main types were distinguished: Concentrated C, Intermediate I, Open O, Line L, Flat F, and cD. The types correspond to the base divisions from regular to irregular clusters, but also note the presence of preferential direction or plane in each cluster.